Geraniol rescues inflammation in cellular and animal models of mevalonate kinase deficiency. - Marcuzzi, Annalisa; Crovella, Sergio; Pontillo, Alessandra (In Vivo, 2011)
BACKGROUND/AIM: The inhibition of the mevalonate pathway through genetic defects such as mevalonate kinase deficiency (MKD) or pharmacological drugs such as aminobisphosphonates causes a shortage of intermediate compounds, in particular geranylgeranyl-pyrophosphate (GGPP), which is associated with the consequent augmented IL-1β release in monocytes. Considering that, due to its biochemical structure, isoprenoid geraniol enters the mevalonate pathway and may revert the genetic or pharmacological inhibition, the present study tested isoprenoid geraniol in cellular and animal MKD models obtained through the use of aminobisphosphonate pamidronate. MATERIALS AND METHODS: The effect of natural isoprenoid geraniol on bacterial induced-inflammation was evaluated in a monocytic cell line (Raw 264.7) and in Balb/c mice treated with pamidronate. RESULTS: Geraniol diminished the levels of inflammatory markers induced by pamidronate stimuli in vitro and in vivo. CONCLUSION: Geraniol may be proposed as a novel therapeutic approach for the orphan disease MKD, and may also be considered for the evaluation of possible inflammatory side-effects of aminobisphosphonates.
Keywords: Animals; Anti-Inflammatory Agents; Cell Line; Diphosphonates; Disease Models, Animal; Inflammation; Lipopolysaccharides; Mevalonate Kinase Deficiency; Mice; Mice, Inbred BALB C; Monocytes; Nitric Oxide; Terpenes